Adiponectin Is a Contributing Factor of Low Appendicular Lean Mass in Older Community-Dwelling Women: A Cross-Sectional Study - Teixeira, Leonardo Augusto Costa; dos Santos, Jousielle Marcia; Parentoni, Adriana Netto; Lima, Liliana Pereira; Duarte, Tamiris Campos; Brant, Franciane Pereira; Neves, Camila Danielle Cunha; Pereira, Fabiana Souza Máximo; Avelar, Núbia Carelli Pereira; Danielewicz, Ana Lucia; Leopoldino, Amanda Aparecida Oliveira; Costa, Sabrina Paula; et al. (Journal of Clinical Medicine, 2022)
inflammaging is a chronic, sterile, low-grade inflammation that develops with advanced age in the absence of overt infection and may contribute to the pathophysiology of sarcopenia, a progressive and generalized skeletal muscle disorder. Furthermore, a series of biomarkers linked to sarcopenia occurrence have emerged. To aid diagnostic and treatment strategies for low muscle mass in sarcopenia and other related conditions, the objective of this work was to investigate potential biomarkers associated with appendicular lean mass in community-dwelling older women. This is a cross-sectional study with 71 older women (75 ± 7 years). Dual-energy X-ray absorptiometry was used to assess body composition. Plasmatic blood levels of adipokines (i.e., adiponectin, leptin, and resistin), tumor necrosis factor (TNF) and soluble receptors (sTNFr1 and sTNFr2), interferon (INF), brain-derived neurotrophic factor (BDNF), and interleukins (IL-2, IL-4, IL-5, IL-6, IL-8, and IL-10) were determined by enzyme-linked immunosorbent assay. Older women with low muscle mass showed higher plasma levels of adiponectin, sTNFr1, and IL-8 compared to the regular muscle mass group. In addition, higher adiponectin plasma levels explained 14% of the lower appendicular lean mass. High adiponectin plasmatic blood levels can contribute to lower appendicular lean mass in older, community-dwelling women.
Number: 23
Keywords: adiponectin; aging; appendicular muscle mass; biomarkers; inflammaging; sarcopenia